Gamification Classroom for Enhancing Students' Computational Thinking Skills in Learning Respiratory System - Resti Rohmah Fatimah, Resti Rohmah (2020)
This research aims to analyze the effect of gamification classroom to enhance students' computational thinking skills on the topic of the respiratory system. The method was designed in such a way as to present a variety of information, with diverse representations of the subject of the respiratory system and direct students to interpret information to build their understanding. Some types of representations used in this study are text, images and videos. In this study, the authors use the Classcraft application as a gamification classroom tool. The student learning process results are then measured to get the results of students' computational thinking skills. The method used in this study was the pre-experimental method (n = 40) of 8th-grade students, with a pretest and posttest one group design. The study results indicate that the gamification classroom method helps students to enhance the computational thinking skills, indicated by the t-test and N-gain value. Based on data analysis, it shows that the average computational thinking skills of students fall into the medium category. With value 0.44 for class A and 0.56 for class B. Furthermore, students' computational thinking skills in aspects of decomposition, abstraction, pattern recognition, and algorithms are categorized as medium. Also, the study results showed that students had a positive impression of gamification classroom by using the Classcraft application. Keywords: Classcraft Application, Gamification Classroom, Student Computational Thinking Skills.